The Inflammatory Status of Soluble Microenvironment Influences the Capacity of Melanoma Cells to Control T-Cell Responses - Bogéa, Gabriela Muller Reche; Silva-Carvalho, Amandda Évelin; Filiú-Braga, Luma Dayane de Carvalho; Neves, Francisco de Assis Rocha; Saldanha-Araujo, Felipe (Frontiers in Oncology, 2022)
The development of immunotherapeutic approaches for the treatment of melanoma requires a better understanding of immunoescape mechanisms of tumor cells and how they interact with other tumor-resident cell types. Here, we evaluated how the conditioned media of resting (rCM) and immune-activated PBMCs (iCM) influence the ability of a metastatic melanoma cell line (MeWo) to control T-cells function. MeWo cells were expanded in RPMI, rCM, or iCM and the secretome generated after cell expansion was identified as MeSec (RPMI), niSec (non-inflammatory), or iSec (inflammatory secretome), respectively. Then, the immunomodulatory potential of such secretomes was tested in PHA-activated PBMCs. iCM induced higher levels of IFN-γ and IL-10 in treated melanoma cells compared to rCM, as well as higher IDO and PD-L1 expression. The iSec was able to inhibit T-cell activation and proliferation. Interestingly, PBMCs treated with iSec presented a reduced expression of the regulators of Th1 and Th2 responses T-BET and GATA-3, as well as low expression of IFN-γ, and co-stimulatory molecules TIM-3 and LAG-3. Importantly, our findings show that melanoma may benefit from an inflammatory microenvironment to enhance its ability to control the T-cell response. Interestingly, such an immunomodulatory effect involves the inhibition of the checkpoint molecules LAG-3 and TIM-3, which are currently investigated as important therapeutic targets for melanoma treatment. Further studies are needed to better understand how checkpoint molecules are modulated by paracrine and cell contact-dependent interaction between melanoma and immune cells. Such advances are fundamental for the development of new therapeutic approaches focused on melanoma immunotherapy.